Volar versus dorsal surgical approaches in fractures of proximal radius in adults: A prospective randomized controlled trial - Rijal, Nishchal; Shrestha, Bikram Prasad; Kalawar, Rosan PS; Pokharel, Bishnu; Baral, Pramod (Journal of Kathmandu Medical College, 2020)
Background: Open reduction and internal fixation with plates and screws is the standard treatment for both-bone forearm fractures in adults. For fractures of the proximal one-third or half of the radius, both the volar (Henry) and dorsal (Thompson) approaches are employed and each one has its own advantages and disadvantages.Objectives: The aim of the study was to compare the functional outcome, intraoperative parameters, complications and duration of union between the two approaches.Methodology: The randomized controlled trial was conducted in the Department of Orthopaedics, B. P. Koirala Institute of Health Sciences (BPKIHS), Dharan, over a period of 12 months (October 2017 to September 2018). Fifty patients with proximal radius fractures were randomized into two groups: Group A and Group B. Patients in Group A (n=25) underwent surgery via the volar approach whereas those in Group B (n=25) via the dorsal approach. They were evaluated on the second postoperative day and at 2, 6, 12 and 24 weeks postoperatively with regards to functional outcome, clinical and radiologic signs of fracture union and complications.Results: The difference in the intraoperative parameters (length of incision, duration of surgery, tourniquet time) was not statistically significant between the two groups (p-values > 0.05). There was a progressive increase in range of motion (ROM) and a progressive decrease in the Disabilities of the Arm, Shoulder and Hand (DASH) scores, signifying improving functional outcome in both the groups during patient follow-up (p-values > 0.05). Three cases of posterior interosseous nerve (PIN) palsies (one in the volar group and two in the dorsal group), one case of deep surgical site infection in the volar group and one case of nonunion in the dorsal group were encountered.Conclusion: The surgical approaches were comparable in terms of functional outcome, intraoperative parameters, complications and time to union. Though cases with PIN palsy were seen in both the groups, the difference in the occurrences was not statistically significant. As both the approaches were associated with a low rate of complications, either can be used based on the preference of the operating surgeon. However, large scale multicenter studies are necessary to recommend guidelines on the choice of surgical approach for proximal radius fractures in adults.